v Valuasi ekonomi budidaya ikan gurame di Desa Beji (menggunakan teknik perhitungan biaya pencegahan dan biaya produktivitas) - Aisyah, Siti; Khasanah, Solikhatun; Wulandari, Sri; Mubedi, Mubedi; Zakaria, Rafli (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
The gourami fish cultivation business in Beji village, KedungBanteng subdistrict, Banyumas district is a business that has great potential to be developed. This research aims to calculate the economic valuation cultivating gourami fish in Beji Village, Kedungbanteng subdistrict and determine the price of natural resources and the environment in the form of water use through the actual market price approach or productivity approach in Beji Village, Kedungbanteng subdistrict. This research is an analytical descriptive research using economic valuation methods. The analytical method used is the Prevention Cost Expenditure Technique and productivity with a population of 18 breeders. Data collection methods using questionnaires and interviews. The results of research from the perspective of prevention and prevention costs show that to determine the number of potential gourami fish using the Productivity Cost Approach Technique, it produces 4,550 kg of gourami fish. Through a productivity approach, researchers identify true market prices. This is done because the natural resources produced can be bought and sold on the market.